A small scale energy harvester from wind induced vibrations - Abdel-Fattah, Ahmed Sayed Ahmed (AUC Knowledge Fountain, 2012)
In this study, a new device for wind energy harvesting on a small-scale was proposed. This system is well suited for powering remote wireless sensors as a cheaper, more environmentally friendly alternative to conventional dry cell batteries which is a need that is being addressed by many recent research studies. The device consists of a cantilever beam with the free end attached to a square section box that is subjected to the air stream inducing aero-elastic flutter. Flutter is a coupled torsion, plunge instability that has been historically studied to be avoided by aerospace and civil engineers. A magnet is attached to the beam and a stationary coil is used to generate electrical power. A finite element model for the device was achieved by formulating a set of ordinary differential equations that integrate the mechanical model of the beam with the aero-elastic flutter of the square section at the tip and the electromagnetic effect of the energy harvesting coil, and they were numerically solved. Wind tunnel experiment runs were carried out for a system with a 30 cm beam and a 30 cm long 5cm wide cross section for wind speeds of 2.4 to 3.2 m/s and electric loads of 40© to 4M©. The numerical predictions were found to compare favorably with the experimental results in terms of the induced voltage, frequency, and power output.